Quanto vale um político? O uso do valor percebido na escolha do político no processo eleitoral - Sodré, Marcelle Chaves (2009)
The reality of contemporary Western democracies, characterized by the weakening of party identity and the rise of the most natural and the personal qualities of the candidate in the orientation of the elections, provoked new electoral behavior and, consequently, further studies that seek explain these policy changes and the voter's behavior more volatile. Given that the perceived value is a strategic imperative in the 1990s to the producers and retailers and is still of importance today. Since it first entered the concept of strategic management, then expanded to the guidelines geared to the client (focuses on the needs and desires of customers) and for the market (considering the market potential and competition), the perceived value has It is the foundation for all marketing activities and that is not to make their segments, such as political marketing? So with the increasing convergence of political marketing with commercial and marketing studies that seek, through the understanding of the attitudes of voters, define the variables that influence their decision making and predict the factors favorable to the achievement of a successful election campaign, this study aims to consider the applicability of the use of "customer perceived value" in the political context and investigate, through the behavioral characteristics of voters, as characterized using the perceived value in the elections. The research is worth qualitative method, with application of Laddering to collect data through indepth interviews, and subsequently using the content analysis to characterize the perceived value in the elections, through the half-chain model end (Means-end Chain Model). 27 items were coded, 9 attributes, 10 consequences and 8 values. The chain is formed by the dominant attribute found "Honesty / Justice," the consequence "correct application of public funds" and values "Better quality of life" and "social welfare". Through its research and other results, we find a more volatile then the actual voters, which seeks to assess the political or even more considering both very personal characteristics of the applicant, related to their image and behavior, as his proposals for party-political campaign. Not noticed in any of the voters any party identification, although the party loyalty of politicians have been raised as a factor of credibility. Indeed, voters have to contemplate the elections not only as a means to promote democracy and improve the life in society, but also to gain personal benefits through means-end chains in this research, the study of the perceptions of voters about the electoral process and their choices.